Novel Alumina–Copper Electrode Composites: Toward Efficient Glutamate and H2O2 Detection - Tatjana Novaković; Dejan Pjević; Nadica Abazović; Zorica Mojović (Compounds, 2025)
Alumina is a well-known catalyst and catalyst support. The electrochemical properties of alumina have recently gained attention. The electrochemical response of alumina greatly depends on the type and number of surface groups present in different alumina types. The surfaces of two types of alumina, anhydrous (A) and trihydrate (T) alumina, were modified by copper through an ion-exchange procedure. The samples were characterized by diffuse reflectance UV–Vis spectroscopy. The obtained samples were used as modifiers of carbon paste electrodes. The electrochemical characterization of the samples was performed using cyclic voltammetry and two redox probes. The electrochemical behavior of samples was investigated in the alkaline and neutral media. The electroanalytical performance of the synthesized composites was tested on glutamate and hydrogen peroxide by linear sweep voltammetry. The functionalization of alumina with copper by ion exchange offered a fast and cost-effective procedure for obtaining a composite with enhanced electrochemical properties for sensing biologically important analytes.